Middle Helladic Tombs at Nydri Plain, Lefkas Island. An Archaeological and Paleoanthropological Study - Staikou, Vivian; Sianis, Panagiotis D.; Vassou, Despoina; Psonis, Nikolaos; Allentoft, Morten E.; Iliopoulos, George (Journal of Greek Archaeology, 2021)
The prehistoric record of Lefkas and the smaller neighboring islands is fairly extensive. The oldest archaeological material dates back to the Middle Palaeolithic period. The Neolithic period is also attested by archaeological finds in five caves. Even though Early (EH) and Middle Helladic (MH) periods have been known since the 1920s due to Dőrpfeld’s excavations, the archaeological data from the Late Bronze Age are scarce. A small Mycenaean tholos tomb has been excavated at Agios Nikitas, while several LH tumuli have been unearthed at the neighboring Meganissi Island.